Effect of the addition of rituximab to salvage chemotherapy prior to autologous stem cell transplant in aggressive CD20+ lymphoma: a cohort comparison from the NCIC Clinical Trials Group Study LY.12*. Issue 1 (2nd January 2017) - Baetz, Tara; Chen, Bingshu E.; Couban, Stephen; Tom Kouroukis, C.; Buckstein, Rena; Kuruvilla, John; Howson-Jan, Kang; Szwajcer, David; Federico, Massimo; Meyer, Ralph M.; Djurfeldt, Marina S.; Hay, Annette E.; et al.
Abstract: The impact of the addition of rituximab to salvage chemotherapy prior to autologous stem cell transplant (ASCT) was evaluated in a retrospective subgroup analysis of NCIC CTG LY.12. Among 414 patients who relapsed following R-CHOP, 96 received salvage chemotherapy alone [R − cohort]; and 318 received rituximab with chemotherapy [R + cohort] following a protocol amendment. The R−cohort had a higher proportion of patients with PS ≥2 and relapse <1 year after R-CHOP. The response rate (45.6% vs. 25.0%, p = 0.0003), CR/CRu (15.7% vs. 4.2%, p = 0.003) and transplantation rate (51.9% vs. 31.3%, p = 0.0004) was higher in the R + cohort. Event-free (27% vs. 22%, p = 0.0954) and overall survival at four years (43% vs. 31%; p = 0.045) were greater in the R + cohort when the patients with best response SD/PD to R-CHOP were excluded. Addition of rituximab to salvage therapy before ASCT appears to improve the response rate, transplantation rate, and overall survival in patients with CD20+ lymphoma who responded to R-CHOP.